Mechanical properties of highly porous Ti49.5Ni50.5 biomaterials. (July 2015) - Kim, Yeon-wook
Abstract: Ti49.5 Ni50.5 shape memory alloy fibers were prepared by a melt overflow process. The martensitic transformation starting temperature of B2 → B19′ in the rapidly solidified fibers was 19 °C. Cylindrical billets of Ni-rich Ti–Ni alloy with 75% porosity were produced by a vacuum sintering technology using as-cast alloy fibers. The mechanical properties and shape memory properties of the highly porous Ti–Ni alloy is investigated using a compressive test. The plateau of the stress–strain curve was observed at about 7 MPa and resulted in 8% elongation associated with stress-induced B2 → B19′ transformation. Because of the high porosity of this specimen, the elastic modulus of about 0.95 GPa could be obtained. It was also found that a recovered strain was 5.9% on heating after the compressive deformation. This recovery of the length is ascribed to the shape memory effect which occurs during the martensitic transformation. Highlights: Rapidly solidified Ti–Ni fibers were fabricated by melt overflow process. Porous Ti–Ni alloys with 75% porosity were prepared by solid state sintering. Plateau of the stress–strain curve was observed at 7 MPa and resulted in 8% elongation. Because of the high porosity, elastic modulus of 0.95 GPa could be obtained.